2002
DOI: 10.1074/jbc.c200170200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitroglycerin on Soluble Guanylate Cyclase

Abstract: Soluble guanylate cyclase (sGC) is a heterodimeric hemoprotein that catalyzes the conversion of GTP to cGMP. Upon binding NO to its heme cofactor, purified sGC was activated 300-fold. sGC was only activated 67-fold by nitroglycerin (GTN) and Cys; and in the absence of Cys, GTN did not activate sGC. Electronic absorption spectroscopy studies showed that upon NO binding, the Soret of ferrous sGC shifted from 431 to 399 nm. The data also revealed that activation of sGC by GTN/Cys was not via the expected ferrous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Specific sGC activity was decreased by approximately 50% upon exposure of the cells to GTN, and the effect of the organic nitrate was prevented by coincubation of the cells with GTN and sepiapterin. Activation of sGC by protoporphyrin IX, which acts through binding to heme-free sGC, was not affected by pretreating the cells with GTN, indicating that the effect of the organic nitrate is due to oxidation of ferrous sGC and subsequent loss of the ferric heme, as suggested previously (Schröder et al, 1988;Schrammel et al, 1996;Artz et al, 2002;Gorren et al, 2005;Schmidt et al, 2010). Thus, the present data suggest that BH4 protects sGC-bound heme against oxidation.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Specific sGC activity was decreased by approximately 50% upon exposure of the cells to GTN, and the effect of the organic nitrate was prevented by coincubation of the cells with GTN and sepiapterin. Activation of sGC by protoporphyrin IX, which acts through binding to heme-free sGC, was not affected by pretreating the cells with GTN, indicating that the effect of the organic nitrate is due to oxidation of ferrous sGC and subsequent loss of the ferric heme, as suggested previously (Schröder et al, 1988;Schrammel et al, 1996;Artz et al, 2002;Gorren et al, 2005;Schmidt et al, 2010). Thus, the present data suggest that BH4 protects sGC-bound heme against oxidation.…”
Section: Resultssupporting
confidence: 68%
“…Both functional and spectroscopic data published previously clearly indicate that GTN and ODQ oxidize the ferrous heme iron of sGC, resulting in loss of NO sensitivity of the enzyme (Schröder et al, 1988;Schrammel et al, 1996;Artz et al, 2002;Gorren et al, 2005;Schmidt et al, 2010). Early studies by Ignarro et al (1982) showed that the heme-free enzyme is activated by protoporphyrin IX, and the new sGC activators, including BAY 60-2770 (Knorr et al, 2008) seem to act as highly potent protoporphyrin IX mimetics that activate heme-free sGC formed subsequent to oxidation by ODQ (Roy et al, 2008;Hoffmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that the decrease in sGC expression elicited by high blood pressure is not exclusively 77 These authors…”
Section: Effects Of Oxidativementioning
confidence: 99%
“…77 The availability of specific activators of heme-oxidized sGC 78 should help to clarify whether or not nitrate tolerance is mediated in part on oxidation of the sGC heme-iron in intact cells.…”
Section: Effects Of Oxidativementioning
confidence: 99%
“…10 -13 The medical use of GTN is limited by the development of tolerance, which occurs following prolonged administration or the application of high doses. This phenomenon has been related to various mechanisms, in particular, desensitization of sGC, 14 and, mainly, impairment of GTN biotransformation by inhibition of ALDH-2. 10 -12 These actions, like others associated with GTN, have been linked to an increase in the production of reactive oxygen species (ROS), 15 as well as mitochondrial dysfunction.…”
mentioning
confidence: 99%